2020
DOI: 10.1002/ehf2.12880
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the relationship between left ventricular ejection fraction and ventricular–arterial coupling

Abstract: The aim of this article was to analyse in-depth the relationship between left ventricular (LV) ejection fraction (EF) (LVEF) and the most commonly used formulas for the calculation of LV elastance (Ees), volume intercept at 0 mmHg pressure (V0), effective arterial elastance (Ea), and ventricular-arterial coupling (VAC) as are validated today. We analyse the mathematical resulting consequences, raising the question on the physiological validity. To our knowledge, some of the following mathematical consequences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
(53 reference statements)
0
6
0
3
Order By: Relevance
“…24 The recent studies also showed that the oversimplified metric such as ESP/ESV-based methods could not substitute the modified single-beat method for the assessment of VAC in critically ill patients, and the simplified Ea formula is another caveat in understanding VAC as the relationship between heart and periphery. 25,26 Therefore, potential inaccuracies may exist. Nonetheless, our results clearly showed that a large population of pediatric patients undergoing VSDs repair has disproportionately elevated Ea to Ees after CPB and that the increase in simplified VAC is associated significantly with poor postoperative outcomes.…”
Section: Discussionsmentioning
confidence: 99%
“…24 The recent studies also showed that the oversimplified metric such as ESP/ESV-based methods could not substitute the modified single-beat method for the assessment of VAC in critically ill patients, and the simplified Ea formula is another caveat in understanding VAC as the relationship between heart and periphery. 25,26 Therefore, potential inaccuracies may exist. Nonetheless, our results clearly showed that a large population of pediatric patients undergoing VSDs repair has disproportionately elevated Ea to Ees after CPB and that the increase in simplified VAC is associated significantly with poor postoperative outcomes.…”
Section: Discussionsmentioning
confidence: 99%
“…However, its significance is controversial, as Vo is only a virtual theoretical value, extrapolated from research invasive studies. Meanwhile, available Vo formulas derived from single-beat determinations non-invasive data have wide, uncertain margins (24).…”
Section: Dimensionless Ratiosmentioning
confidence: 99%
“…However, VAC has a more dynamic behavior than LVEF being a valuable tool in heart failure with reduced ejection fraction (HFrEF) and/or unstable hemodynamic situations. LVEF and VAC have a well-proven negative correlation but are not reducible to a simple formula (24). Less frequently, the VAC is calculated by the inverse ratio (Ees/Ea), the relation between the two ratios being like comparing x to 1/x.…”
Section: Dimensionless Ratiosmentioning
confidence: 99%
“…Claramente, la inclusión de cualquier variable clínicamente relevante, compensa la pérdida inherente al uso focalizado de la FE. Algunos ejemplos, se refieren al uso del acoplamiento ventrículo-arterial 7 , el VFS 27 , o la masa miocárdica 28 . Incluso, cuando se estudia pacientes con insuficiencia cardíaca con FE de rango medio, entre 40-50% (ver triángulo de color púrpura en la Figura 4), se ha documentado una enorme heterogeneidad, lo que desvía la atención a otros factores, más allá del uso de la Figura 6.…”
Section: Discussionunclassified
“…Algunas discusiones críticas sobre la FE, se han publicado recientemente en la literatura 6,7 , y es de esperar que tales advertencias se mantengan, hasta que el defecto fundamental de la FE sea reconocido. En el presente artículo, se analiza la estructura matemática de la relación FE y se discuten sus implicancias.…”
unclassified